المسؤولية المدنية الناشئة عن استخدام تقنيات الذكاء الاصطناعي في التشريع الجزائري - ميمون سفيان - لعمارة طارق زياد (جامعة المسيلة, 2024)
The civil liability for the use of artificial intelligence is a new topic in Algeria. Due to the absence of regulatory legislation, clear laws are necessary to define responsibility for damages resulting from the use of this technology Additionally, all stakeholders, including individuals and institutions, must be aware of the risks associated with artificial intelligence and their obligations when using it Our study aims to demonstrate the extent to which legal entities acquire responsibility for artificial intelligence.
Keywords: Civil responsibility; Artificial intelligence (AI); Legal personality